Jesus was a migrant - Cornell, Deirdre (Maryknoll, New York : Orbis Books, 2014)
The Bible is rich in powerful stories of migrants: the children of Israel who wandered the desert; and even the Holy Family, who fled to Egypt. America is a land of immigrants, a land of both opportunities and challenges. Here, Deirdre Cornell reflects on the life of the migrant and the Christian life, and considers how the suffering that accompanies the migrant journey can also be a source of great blessing, for both the travellers and the society that welcomes them.
Migrants matter -- From exile to exodus -- The Great Hunger -- Of meals and journeys -- An Advent lullaby -- Socks for Juan -- Epiphanies in a trailer park -- A dormitory annunciation -- Family album -- One migrant's psalm -- On Nightingale Mountain -- Welcome, Holy Family -- Food for the journey -- And you welcomed me -- At Ellis Island -- Pure grace.
Includes bibliographical references.
Keywords: Emigration and immigration -- Religious aspects -- Christianity; Emigration and immigration -- Religious aspects -- Catholic Church; Church work with immigrants -- United States; Church work with immigrants -- Catholic Church